Photosensitizing effect of benzene oxidation intermediates on the action spectra of Bi2WO6/TiO2-N composites - Morozova, Maria E; Lyulyukin, Mikhail Nikolaevich; Selishchev, Dmitry S; Kozlov, Denis Vladimirovich (Mendeleev communications, 2025)
The dependence of the photonic efficiency on the wavelength, i.e. the action spectrum, was established for the test reactions of benzene and cyclohexane oxidation over the Bi2WO6/TiO2-N composites and individual components. It was found that the action spectrum curve for cyclohexane oxidation reproduces the light absorption curve, while that for benzene oxidation indicates some additional activity in the range of 400--550 nm. It was concluded that the intermediate products of benzene oxidation on the catalyst surface exert a photosensitization effect, which significantly increases the photoactivity of Bi2WO6/TiO2-N composites in the visible range.